2021
DOI: 10.1186/s13046-021-01905-x
|View full text |Cite
|
Sign up to set email alerts
|

ATAD2 interacts with C/EBPβ to promote esophageal squamous cell carcinoma metastasis via TGF-β1/Smad3 signaling

Abstract: Background Distant metastasis is the leading cause of death for esophageal squamous cell carcinoma (ESCC) with limited treatment options and unsatisfactory effectiveness. Bromodomain (BRD) containing proteins are emerging targets for cancer therapy with promising effects. As a unique member of BRD family, the function and molecular mechanism of ATAD2 in cancer development is seldomly investigated. Methods The clinical impact of ATAD2 was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Surgical removal is the conventional treatment for most types of ESCA. However, many patients still show local recurrence or distant metastasis within a short time after surgery [2,3]. Although surgery, radiotherapy, and chemotherapy have improved the survival rate of ESCA patients, the prognosis of ESCA remains poor, and the current 5-year overall survival (OS) rate is only 15%-25% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical removal is the conventional treatment for most types of ESCA. However, many patients still show local recurrence or distant metastasis within a short time after surgery [2,3]. Although surgery, radiotherapy, and chemotherapy have improved the survival rate of ESCA patients, the prognosis of ESCA remains poor, and the current 5-year overall survival (OS) rate is only 15%-25% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the regulatory potential score and data support of C/EBPβ are prominent ( Figure 7 A). As an important transcription factor, C/EBPβ has been reported to participate in physiological activities such as neural signal transduction, cell proliferation, and epidermal-mesenchymal transition by regulating the expression of APOE, TGFβ1, and α-SMA ( Xia et al., 2021 ; Cao et al., 2021 ; Ding et al., 2021 ). This is related to the pathogenesis of Alzheimer’s disease, cancer, fibrosis, and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the loss of ATAD2 results in decreased protein expression of EMT to impede cancer cell migration and invasion 43 . Silencing ATAD2 inhibited ESCC cell growth and lung metastasis in vivo , and the knockdown of ATAD2 inhibited ESCC migration and invasion in vitro 41 . Additionally, the reduction in ATAD2 could induce a decrease in N-cadherin and Vimentin and an increase in E-cadherin, which is also beneficial for metastasis inhibition 44 (Figure 3 E) .…”
Section: Atad2 In Cancermentioning
confidence: 94%
“…While in lung adenocarcinoma, the knockdown of ATAD2 affects glucose metabolism in cancer cells by regulating [18F] FDG uptake and lactate production through the AKT-GLUT1 / HK2 pathway 39 . In addition, silencing ATAD2 also inhibits the growth and colony formation ability of esophageal squamous cell carcinoma (ESCC) cells, and significantly inhibits ESCC tumor growth in vitro 41 .…”
Section: Atad2 In Cancermentioning
confidence: 99%